Does short-term virologic failure translate to clinical events in antiretroviral-naïve patients initiating antiretroviral therapy in clinical practice? - Mugavero, Michael J; May, Margaret; Harris, Ross; Saag, Michael S; Costagliola, Dominique; Egger, Matthias; Phillips, Andrew; Günthard, Huldrych F; Dabis, Francois; Hogg, Robert; de Wolf, Frank; Fatkenheuer, Gerd; et al. (AIDS (London, England), 2008)
To determine whether differences in short-term virologic failure among commonly used antiretroviral therapy (ART) regimens translate to differences in clinical events in antiretroviral-naïve patients initiating ART.
Keywords: Adolescent; Adult; Anti-Retroviral Agents; Disease-Free Survival; Drug Interactions; Drug Resistance, Viral; Drug Therapy, Combination; Epidemiologic Methods; Female; HIV Infections; HIV-1; Humans; Male; Middle Aged; Odds Ratio; Reverse Transcriptase Inhibitors; RNA, Viral; Treatment Outcome; Viral Load; Young Adult